Implementation of Coordination Policy for Forest and Land Fire Control Task Units in Riau Province - Iman Sukendar; Khasan Effendy; Kusworo Kusworo; Udaya Madjid (Budapest International Research and Critics University, 2021)
Forest and Land Fires in Riau Province are still happening today, this happens because of many factors ranging from natural factors and human factors. The method used in this study uses qualitative research methods. The results showed that the coordination of the Karhutla task force in controlling forest and land fires in Riau Province in 2020 involved many stakeholders, especially local stakeholders, the implementation of coordination policies in forest fire control was not optimal because the coordination process had a long span of control. Then the author offers a combination model of policy implementation with a dynamic coordination model. This dynamic coordination model will make decision making in forest and land fire control more targeted and reduce the long span of control so that the implementation of forest and land fire control in the future will be more optimal.